Impact of IBR Location and Parameters on Inter-Area Oscillation Modes in Bulk Power Grids - Shuchismita Biswas; Xue Lyu; Quan Nguyen; Xiaoyuan Fan; Minghui Lu; Wei Du (IEEE Access)
To ensure safe and reliable operations, electric utilities must understand how power grid dynamics are evolving as the existing synchronous machine-dominated systems incorporate increasing amounts of inverter-based resources (IBRs). A pressing concern is understanding if and how the well-known inter-area modes of oscillation will change due to increasing inverter penetration. To address this question, this paper derives an explicit analytical expression to identify the major factors influencing changes in inter-area mode properties when synchronous machines are replaced by IBRs. The IBRs are assumed to implement droop-based grid forming (GFM) control, while the analysis can be extended to other inverter control methods. It is concluded that oscillation mode changes are highly dependent on the grid location where synchronous machines are removed and/or IBRs are added, and the observed changes can be mitigated, to some extent, by tuning two of the GFM inverter control parameters, namely 1) the active power-frequency droop coefficient; and 2) the time constant of the active power measurement low-pass filter. The analytical conclusions are validated using full dynamic simulations of the IEEE 39-bus benchmark system, and the 2031 heavy-winter planning model of the US Western Interconnection. Conclusions from this study will help utilities understand 1) if/which inter-area modes will continue to be of concern in their footprints in an IBR-dominated future, and 2) identify areas where the displacement of synchronous machines may significantly alter the properties of existing modes, necessitating additional analysis during interconnection studies.